Distributed Optimization Strategy for Voltage Regulation in PV-Integrated Power Systems with Limited Sensor Deployment - Lu, Xun; Liu, Junlei; Liu, Xinmiao; Liu, Jun; Lin, Lingxue (Energies (Basel), 2025)
This paper presents a distributed optimization strategy for reactive power–voltage control in distribution networks with high photovoltaic (PV) penetration under limited sensor deployment scenarios. To address voltage violations and minimize network power losses, a novel distributed optimization framework is developed that utilizes selective nodal measurements from PV-integrated nodes and critical T-junction locations, coupled with inter-node communication for information exchange. The methodology integrates an adaptive step size algorithm within a dynamic projected primal–dual distributed optimization framework, eliminating manual parameter tuning requirements while ensuring theoretical convergence guarantees through Lyapunov stability analysis. Comprehensive validation on the IEEE 33-bus distribution test system demonstrates that the proposed strategy achieves significant performance improvements. The distributed control framework reduces measurement infrastructure requirements while maintaining near-optimal performance, demonstrating superior economic efficiency and operational reliability. These results establish the practical viability of the proposed approach for real-world distribution network applications with high renewable energy integration, providing a cost-effective solution for voltage regulation under incomplete observability conditions.